2020
DOI: 10.1038/s41598-020-77060-8
|View full text |Cite
|
Sign up to set email alerts
|

Ravens parallel great apes in physical and social cognitive skills

Abstract: Human children show unique cognitive skills for dealing with the social world but their cognitive performance is paralleled by great apes in many tasks dealing with the physical world. Recent studies suggested that members of a songbird family—corvids—also evolved complex cognitive skills but a detailed understanding of the full scope of their cognition was, until now, not existent. Furthermore, relatively little is known about their cognitive development. Here, we conducted the first systematic, quantitative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(24 citation statements)
references
References 105 publications
(168 reference statements)
0
24
0
Order By: Relevance
“…Similarly, a genetic component is apparent in New Caledonian (Rutz & St Clair, 2012) and Hawaiian (Rutz et al, 2016) crows, which develop tool use in (nearly) all individuals without social input. Although tool use is typically viewed as a product of individual learning in birds (Bandini & Tennie, 2020), ravens were likely also affected by social factors in these observations, such as local or stimulus enhancement towards apparatuses and tools (Beck et al, 2020;Lambert et al, 2019;Miller et al, 2016;Pika et al, 2020;Stöwe et al, 2006).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Similarly, a genetic component is apparent in New Caledonian (Rutz & St Clair, 2012) and Hawaiian (Rutz et al, 2016) crows, which develop tool use in (nearly) all individuals without social input. Although tool use is typically viewed as a product of individual learning in birds (Bandini & Tennie, 2020), ravens were likely also affected by social factors in these observations, such as local or stimulus enhancement towards apparatuses and tools (Beck et al, 2020;Lambert et al, 2019;Miller et al, 2016;Pika et al, 2020;Stöwe et al, 2006).…”
Section: Discussionmentioning
confidence: 98%
“…establishing contact between tool and food, and never moving the tool sideways). Many corvids, including ravens, spontaneously solve instrumental problem when they are not responsible for establishing contact with the target (Heinrich, 1999a; Jacobs & Osvath, 2015; Lambert et al, 2019; Pika et al, 2020; Shumaker et al, 2011).…”
Section: Observationsmentioning
confidence: 99%
“…However, this influence was not detected. This is probably due to the fact that full-blown cognitive skills are formed in corvids by the age of 4 months and do not change significantly at the age of 8, 12, and 16 months ( Pika et al, 2020 ). All our crows were over a year old.…”
Section: Discussionmentioning
confidence: 99%
“…It is also important to pay attention to the linkage between ontogeny and cognitive performance of corvids. A 2020 study using the Primate Cognition Test Battery (PCTB) demonstrated that full-blown cognitive skills are found as early as 4 month old ravens and do not change at later ages ( Pika et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…There have been some recent attempts to adapt the primate cognition test battery (Herrmann et al, 2007)—originally developed as a standardised way to compare the cognition of great ape species—for avian species, with mixed success (Krasheninnikova et al, 2019; Pika et al, 2020). Ultimately, even when modifications are made, the test battery was originally designed to reflect the natural challenges faced by primates, meaning it lacks ecological relevance for distantly related species.…”
Section: Field-specific Challengesmentioning
confidence: 99%